2022
DOI: 10.1155/2022/2091791
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FABP7 as a Potential Biomarker for Predicting Prognosis and Antiangiogenic Drug Efficacy of Glioma

Abstract: Objective. Glioma is a common malignant tumor of the central nervous system with extremely poor prognosis. An efficient molecular marker for diagnosis and treatment is urgently needed. Fatty acid binding protein 7(FABP7), which regulates intracellular lipid metabolism, is highly expressed in nervous system tumors, but its prognostic value remains undetermined. The present study investigated the relationship between FABP7 expression and prognosis in glioma patients by bioinformatics analysis, as well as immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Studies have shown that FABP7 is involved in the occurrence and development of various tumors and can serve as a prognostic marker for tumors. FABP7 is highly expressed in malignant glioma, breast cancer and renal cell carcinoma, promoting their proliferation, migration and invasion, and is related to the poor prognosis of patients [11][12][13] . In addition, FABP7 plays a key role in the metabolic reprogramming of HER2 + breast cancer cells, supporting the glycolysis phenotype and lipid droplet storage, enabling them to adapt and survive in the brain microenvironment [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that FABP7 is involved in the occurrence and development of various tumors and can serve as a prognostic marker for tumors. FABP7 is highly expressed in malignant glioma, breast cancer and renal cell carcinoma, promoting their proliferation, migration and invasion, and is related to the poor prognosis of patients [11][12][13] . In addition, FABP7 plays a key role in the metabolic reprogramming of HER2 + breast cancer cells, supporting the glycolysis phenotype and lipid droplet storage, enabling them to adapt and survive in the brain microenvironment [14] .…”
Section: Introductionmentioning
confidence: 99%